2020
DOI: 10.1038/s41467-020-18454-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular bacterial lymphatic metastasis drives Streptococcus pyogenes systemic infection

Abstract: Unassisted metastasis through the lymphatic system is a mechanism of dissemination thus far ascribed only to cancer cells. Here, we report that Streptococcus pyogenes also hijack lymphatic vessels to escape a local infection site, transiting through sequential lymph nodes and efferent lymphatic vessels to enter the bloodstream. Contrasting with previously reported mechanisms of intracellular pathogen carriage by phagocytes, we show S. pyogenes remain extracellular during transit, first in afferent and then eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 83 publications
1
49
0
Order By: Relevance
“…Bacterial colonization occurs in mucosal membranes of the oropharynx and non-intact skin; for disease to develop, bacterial cells first adhere and later internalize the host cells ( Fiedler et al, 2015 ). Very recently, Siggins showed that in severe invasive infections, S. pyogenes reach the bloodstream using efferent postnodal lymphatic vessels through sequential draining lymph nodes ( Siggins et al, 2020 ). The authors also showed that while traveling form the primary site of infection, the bacteria remains extracellular.…”
Section: Clinical and Veterinary Relevance Of Pyogenic Biofilmmentioning
confidence: 99%
“…Bacterial colonization occurs in mucosal membranes of the oropharynx and non-intact skin; for disease to develop, bacterial cells first adhere and later internalize the host cells ( Fiedler et al, 2015 ). Very recently, Siggins showed that in severe invasive infections, S. pyogenes reach the bloodstream using efferent postnodal lymphatic vessels through sequential draining lymph nodes ( Siggins et al, 2020 ). The authors also showed that while traveling form the primary site of infection, the bacteria remains extracellular.…”
Section: Clinical and Veterinary Relevance Of Pyogenic Biofilmmentioning
confidence: 99%
“…In healthy individuals, bacteria frequently breach epithelial barriers and enter into the circulatory system, but are rapidly eliminated by complement and other humoral factors and/or captured and killed by liver- and spleen-resident phagocytic cells, clearing the infection and preventing sustained bacteremia ( Jenne and Kubes, 2013 ; Krenkel and Tacke, 2017 ). However, some pathogenic bacteria can at least temporarily evade or resist these host defenses to potentially enable subsequent dissemination ( Smith et al, 2010 ; Armbruster et al, 2019 ; Holmes et al, 2021 ; Ercoli et al, 2018 ; Gresham et al, 2000 ; Siggins et al, 2020 ). Extraintestinal pathogenic Escherichia coli (ExPEC) , a set of pathogenic E. coli isolates that cause disease outside of the intestine, are the leading causes of bacteremia in humans ( Dale and Woodford, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long regarded as a predominantly extracellular pathogen, GAS can disseminate into deeper tissues by creating a highly inflammatory environment at the site of infection and degrading intercellular junctions (Sumitomo, Nakata, Higashino, Terao, & Kawabata, 2013; Sumitomo, Nakata, Higashino, Yamaguchi, & Kawabata, 2016). A recently discovered tropism for lymphatic tissues allows GAS to further spread through the body by entering the lymphatic system (Lynskey et al, 2015; Siggins et al, 2020). In addition, several studies have reported the ability of GAS to persist in the intracellular compartment of epithelial and endothelial cells, macrophages and neutrophils (Barnett et al, 2013; Burns Jr., Lukomski, Rurangirwa, Podbielski, & Musser, 1998; Jadoun et al, 1998; LaPenta, Rubens, Chi, & Cleary, 1994; Medina, Rohde, & Chhatwal, 2003; Soderholm et al, 2018; Thulin et al, 2006), which may contribute to GAS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%